Logics of the Icelandic Hybrid Media System: Snapchat and media-use before the 2016 and 2017 Althing elections - Guðmundsson Birgir (Nordicom Review, 2019)
The increased importance of social media platforms and network media logic merging with traditional media logic are a trademark of modern hybrid systems of political communication. This article looks at this development through the media-use by politicians before the 2016 and 2017 parliamentary elections in Iceland. Aggregate results from candidate surveys on the use and perceived importance of different media forms are used to examine the role of the new platform Snapchat in relation to other media, and to highlight the dynamics of the hybrid media system in Iceland. The results show that Snapchat is exploited more by younger politicians and those already using social media platforms. However, in spite of this duality between old and new media, users of traditional platforms still use new media and vice versa. This points to the existance of a delicate operational balance between different media logics, that could change as younger politicians move more centre stage.